Spinal cord oligodendrocytes develop from ventrally derived progenitor cells that express PDGF alpha-receptors. - Hall,A; Giese,NA; Richardson,WD (Development, 1996)
Platelet-derived growth factor alpha-receptors (PDGFR alpha) are expressed by a subset of neuroepithelial cells in the ventral half of the embryonic day 14 (E14) rat spinal cord. The progeny of these cells subsequently proliferate and migrate into the dorsal parts of the cord after E16. Here, we show that E14 ventral cells are able to generate oligodendrocytes in culture but that dorsal cells acquire this ability only after E16, coinciding with the appearance of PDGFR alpha-immunoreactive cells in the starting population. PDGFR alpha-positive cells in optic nerve and spinal cord cultures co-labelled with antibody markers of oligodendrocyte progenitors. When PDGFR alpha-positive cells were purified from embryonic rat spinal cords by immunoselection and cultured in defined medium, they all differentiated into oligodendrocytes. Very few oligodendrocytes developed in cultures of embryonic spinal cord cells that had been depleted of PDGFR alpha-expressing cells by antibody-mediated complement lysis. These data demonstrate that all PDGFR alpha-positive cells in the embryonic rat spinal cord are oligodendrocyte progenitors and that most or all early-developing oligodendrocytes are derived from these ventrally-derived precursors.